Is the management of obesity in primary health care appropriate in Brazil? - Mariana Souza Lopes; Patrícia Pinheiro de Freitas; Maria Cecília Ramos de Carvalho; Nathália Luíza Ferreira; Mariana Carvalho de Menezes; Aline Cristine Souza Lopes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: This study aims to describe the adequacy of basic health units (UBS) in Brazil regarding structure and work process for obesity management and to evaluate user satisfaction with primary health care services. This cross-sectional study was conducted with data from the 2013-2014 National Program for Improving Primary Care Access and Quality (PMAQ) - an initiative to assess primary health care teams' performance. Data were collected between 2013 and 2014 through interviews with primary health care teams and users. All indicators of adequate care for obesity were defined within the article scope, based on data from the PMAQ. Of the 24,055 UBS analyzed, located in 4,845 different cities, only 7.6% had adequate structure for obesity management. Likewise, only 26.6% of the 114,615 users interviewed reported adequate access, and 27.8% of the UBS showed adequate service organization. Healthcare was considered as "good" or "very good" by 82.4% of users. These indicators varied according to geographic region, showing better results for the South and Southeast. Our results suggest that the country may still be at the initial stage of systematizing care with obesity, presenting significant disparities among regions.